The Impact of Job Stress on Job Performance among Operational Level Employees of Two Selected Electrical Manufacturing Companies in Colombo District, Sri Lanka - Jayasooriya, K.P.L.M.; Gamage, A.S. (My University, 2017)
Attached

This study attempts to identify the impact ofjob stess on job performance among operational level employees of two selected electrical manufachring connpanies in Colornbo diskict. There is an enpirical knowledge gap in Sri Lankan context on the irnpact ofjob shess on job performance of operational level e,mplo-vees in electrical rnanufacturing companies. This study aimed to investigate the impact of job skess on.job performance among operational level ernployees of two selected electrical manufacturirg companies in Colombo district. The data were collected &om a randorrrtry seXected sample of 108 operational level employees of two selected electrical manufacturing companies located in Colcrnbo district by adnainistering a structured questionnaire, which consisted of'38 questionsl statements with 5 point scale. The data analysi.s included the rinivariate and bivariate analyses. "fhis study found that there is a strong positive relationship between workload and job performance and there is a weak negative reiationship between role conflict and role ambiguity with the job performance among operational level employees of the two selected eleckical manufacfuriag companies. It is concluded that the worktroad is positiveiy associated with job performance while role conflict and rotre ambiguif are negatively associated with the job perfomrance among operational level enrpioyees of two setrected eleckical manufacturing companies in Colombo district, Sri Lanka. Thus, job performaaee of employee is significantly based on the job stress. Hence, it can be concluded that job stress is a major factor which can affect the job perforrnance of the all operational level employ€es in the electrical manufacturing industy and the management of the eleckical rnariufacturing cornpanies has to consider to minimize &e job stress of the operational level workem introducing appropriate strategies.
Keywords: Job Stress, Workload, Role Conflicts, Role Ambiguity, Job Performance, Production Assistants